Diagnostic Biotechnical System of the Quantitative Diagnostics of Malabsorption - Sokol, Yevgen I.; Lapta, Stanislav S.; Chmykhova, Oksana V.; Solovyova, Olga I.; Goncharova, Olga (Institute of Electrical and Electronics Engineers, 2017)
An algorithmic block of biotechnical system of the quantitative diagnostics of glucose malabsorption on the base of conversion of the oral glucose to lerance test glycemic data into the necessary diagnostical parameters by the use of the original mathematical model of the carbohydrate metabolism regulation system was elaborated. A new diagnostic parameter, characterising a degree of glucose absorption in the intestine, was suggested as well as the criteria on it. Diagnostics on the new parameter was compared with the diagnostics by means of “sugar loads” and “glucose absorption intensity” methods.
Keywords: diagnostics of glucose malabsorption; mathematical model; carbohydrate exchange; regulation system.